2023
DOI: 10.59717/j.xinn-life.2023.100038
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional biomanipulation: A powerful ecotechnology to combat cyanobacterial blooms in eutrophic freshwaters

Jun Chen,
Jiarui Liu,
Shengpan Han
et al.

Abstract: <p>Cyanobacterial blooms, occurring frequently in eutrophic freshwaters worldwide, are considered as potential hazards to ecosystems and human health, and it is often difficult and expensive to control their outbreaks in large lakes through reduction of nutrient loadings. Biomanipulation, launched as an ecology-based solution in the 1970s, was once believed to be an effective way to counteract cyanobacterial blooms. It is divided into traditional biomanipulation (TB) and nontraditional biomanipulation (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Global biodiversity loss in freshwater ecosystems has increased during the past decades due to the intensification of human activities such as land use change, environmental pollution, species invasion, and climate changes. [8][9][10][11] As species diversity has been widely recognized to play a major role in influencing ecosystem functioning and stability, 12,13 ecologists generally support the positive biodiversity-stability relationship, where higher species diversity is expected to buffer the risk of ecosystem collapse. 14,15 Nonetheless, this idea was challenged by the modeling work of May, who found that species diversity has negative relationships with ecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…Global biodiversity loss in freshwater ecosystems has increased during the past decades due to the intensification of human activities such as land use change, environmental pollution, species invasion, and climate changes. [8][9][10][11] As species diversity has been widely recognized to play a major role in influencing ecosystem functioning and stability, 12,13 ecologists generally support the positive biodiversity-stability relationship, where higher species diversity is expected to buffer the risk of ecosystem collapse. 14,15 Nonetheless, this idea was challenged by the modeling work of May, who found that species diversity has negative relationships with ecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical control methods play a role in many specific environments, but most of them are costly, inefficient, and ecologically damaging compared to biological control methods. Biological methods include aquatic plant management, biological filter feeding, algae management, and microbiological management [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%